Effect of Risk Factors on Blood Pressure Using Multivariate Model amongst Adult Tribal Population in a District of India - Nisha Meshram; Swapnil V. Shinkar; Nirmal Verma; Neha Shrivastava (Preventive Medicine: Research & Reviews)
Background: This research study uses multivariate model to analyse the effect of various risk factors on blood pressure (BP) levels amongst adults in the tribal communities. Materials and Methods: A community-based cross-sectional observational study with adult tribal population residing in Lohandiguda, Bastar district, Chhattisgarh, India. A multistage sampling was followed and the modified World Health Organization questionnaire for hypertensive patients was used. Results: Three hundred and thirty adults were included. Positive moderate-weak correlation in all three groups shown by body mass index (BMI) (0.208, 0.214 and 0.287) and waist–hip ratio (WHR) (0.223, 0.240 and 0.359) with systolic BP and (BMI = 0.223, 0.240 and 0.240; WHR = 0.166, 0.198 and 0.288) diastolic BP, respectively, was found. The Pearson correlation coefficient shows that the highest predictor of high BP was BMI (0.226) followed by WHR (0.198), age (0.182), number of bidi/cigarette use per day (0.131) and smokeless tobacco frequency per day (0.114). The multivariate general linear model is moderately distinguishable (0.529) amongst all study subjects and (0.543) amongst addicted study subjects with BP having strong significance (0.000) each for addicted and overall study subjects. Conclusion: These findings call for careful consideration in the development of dietary recommendations, quitting addictions, increased attention on physical activities and public health policies tailored to tribal communities.